Mesenchymal stem cells and their mitochondrial transfer: a double-edged sword. Issue 5 (3rd May 2019) - Li, Cheng; Cheung, Marco K.H.; Han, Shuo; Zhang, Zhao; Chen, Ling; Chen, Junhui; Zeng, Hui; Qiu, Jianxiang
Abstract : Mitochondrial dysfunction has been linked to many diseases including organ degeneration and cancer. Mesenchymal stem cells/stromal cells (MSCs) provide a valuable source for stem cell-based therapy and represent an emerging therapeutic approach for tissue regeneration. Increasing evidence suggests that MSCs can directly donate mitochondria to recover from cell injury and rescue mitochondrial damage-provoked tissue degeneration. Meanwhile, cancer cells and cancer stromal cells also cross-talk through mitochondrial exchange to regulate cancer metastasis. This review summarizes the research on MSCs and their mitochondrial transfer. It provides an overview of the biology, function, niches and signaling that play a role in tissue repair. It also highlights the pathologies of cancer growth and metastasis linked to mitochondrial exchange between cancer cells and surrounding stromal cells. It becomes evident that the function of MSC mitochondrial transfer is a double-edged sword. MSC mitochondrial transfer may be a pharmaceutical target for tissue repair and cancer therapy.